Identification of causal agent of blossom blight of loquat in Zhejiang Province, China - SUN Hu; ZHANG Li-li; ZHANG Jing-ze; HU Dong-wei (浙江大学学报. 农业与生命科学版, 2009)
The blossom blight of loquat occurred severely in 2007 in loquat orchards in Deqing County, Jiaxing District, Zhejiang Province of China, causing the flower spike wilt and death of loquat. To identify the causal agent, six Botrytis sp. isolates were obtained from the diseased flower spikes of loquat. Based on morphological and cultural characters, the isolates were identified as Botrytis cinerea Pers, and its teleomorph is Botryotinia fuckeliana Whetzel. By analysis of nucleotide sequences of the ITS regions of ribosomal DNA (ITS1 and ITS2) and the 5.8S RNA gene, the sequences of isolates were 100% identical to that of B. fuckeliana, further confirming that the pathogen was B. cinerea. Pathogenicity test showed that B. cinerea isolates were able to infect the flower spikes of loquat, causing the symptoms to be similar to natural hosts.